Modeling of multiwall carbon nanotubes reinforced natural rubber for soft robotic applications – A comprehensive presentation. (2021) - Natarajan, Elango; Hassan, C.S.; Chun Kit, Ang; Santhosh, M.S.; Ramesh, S.; Sasikumar, R.
Abstract: Soft materials like rubbers, polymers and elastomers are non-linear hyper elastic materials or visco-elastic materials that show the large deformation under loading. One of the nonlinear material model is to be used in the simulation of soft mechanism. Mooney-Rivlin, Ogden, Polynomial, Arruda-Boyce, Yeoh, and Neo-Hookean and Extended Tube are some nonlinear hyperelastic material models existing in the practice. The objexctive of the current research is to present comprehensively the nonlinear material constants of the multiwall nanocarbon (MWCNT) reinforced natural rubber (NR) composites. NR/MWCNT composites with 5%, 10%, 20% and 30% weight fractions of MWCNTs are prepared through compression molding. The uniaxial tensile test was conducted on dumb bell specimens of ASTM D412-06a standard. The respective strain–stress data from uni-axial tensile tests are further curve fitted into existing popular nonlinear hyperelastic models. The nonlinear constants of respective model are comprehensively tabulated, which designers can use in the component design and analysis. Finite element contact analysis of a cylindrical soft finger pressed against a rigid plate is conducted and presented.